Faktor Yang Mempengaruhi Pemahaman Pengelolaan Keuangan Desa Di Kecamatan Palibelo Kabupaten Bima - Nurhidayah, Rizki; Suhaedi, Wirawan; Suryantara, Adhitya Bayu (Jurnal Riset Mahasiswa Akuntansi, 2024)
This study aims to determine the effect of Education Level, work experience of village officials, and the quality of training on the understanding of Village Financial Management in Palibelo District, Bima Regency. The research method used is associative research method. Primary Data will be used as a source of data through questionnaire data collection methods. The population of this study is the understanding of village financial managers in the District Palibelo. Sampling technique using purposive sampling. The criteria for sampling are village officials who play a direct role in understanding village financial management, such as village heads, secretaries, treasurers, village consultative bodies and head of government. Data analysis method using multiple regression analysis using SmartPLS. The results of this study indicate that the level of education, work experience of village administrators, and the quality of training partially affect the understanding of Village Financial Management. This study contributes to improving the quality of understanding of village financial management by the village government and the Regent government by increasing the level of education, experience of village officials, and the quality of training on understanding Village Financial Management.